2010
DOI: 10.1210/jc.2009-2255
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training in Pregnancy Reduces Offspring Size without Changes in Maternal Insulin Sensitivity

Abstract: Regular exercise was associated with lower birth weights and reduced cord concentrations of growth-related peptides, suggesting an influence of exercise on endocrine regulation of fetal growth. These effects on offspring growth were not associated with an exercise training effect on maternal insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
225
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(240 citation statements)
references
References 29 publications
7
225
0
8
Order By: Relevance
“…Although shifting the occurrence of a large for gestational age baby to a normal range has benefits for maternal outcomes, elevated birth weight is not always observed and therefore cannot always be assumed in human studies or animal models of maternal over-nutrition. Indeed, birth weight data in the above mentioned studies [24][25][26][27] and our recent review of maternal high-fat feeding and offspring development show birth weight is often similar between offspring groups or in fact lower in offspring of obese mothers compared with controls. 28 A major limitation of human studies is the degree to which a mechanistic understanding may be achieved without invasive procedures in children.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 97%
See 1 more Smart Citation
“…Although shifting the occurrence of a large for gestational age baby to a normal range has benefits for maternal outcomes, elevated birth weight is not always observed and therefore cannot always be assumed in human studies or animal models of maternal over-nutrition. Indeed, birth weight data in the above mentioned studies [24][25][26][27] and our recent review of maternal high-fat feeding and offspring development show birth weight is often similar between offspring groups or in fact lower in offspring of obese mothers compared with controls. 28 A major limitation of human studies is the degree to which a mechanistic understanding may be achieved without invasive procedures in children.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 97%
“…Increasing attention towards interventions that may be used to improve maternal health could, therefore, impact substantially on offspring health both in the short and long term. A number of early reviews, 19,[22][23][24][25] in addition to two recent studies, 26,27 have identified altering maternal carbohydrate intake as well as maternal physical activity levels as potential strategies for positively regulating maternal weight gain and offspring birth weight among other pregnancy outcomes. However, longitudinal studies that describe the potential long-term benefits of these interventions for offspring health are lacking.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 99%
“…Thus, regular aerobic exercise during pregnancy seems to lead to a small reduction in offspring birth weight when compared with the offspring of nontraining women, which could be explained by maternal hormonal alterations, the regulation of nutrient availability for fetal growth through placenta, and epigenetic processes (Hopkins et al, 2010). However, these effects on offspring growth were not associated with changes in maternal insulin sensitivity (during a healthy pregnancy) and no effects in offspring body composition were found (Hopkins et al, 2011).…”
Section: Physical Activitymentioning
confidence: 99%
“…Male and female offspring of mothers who exercised during pregnancy show lower birth growth rates and reduce umbilical cord concentrations of serum IGF-1 (growth promoting factor, especially in children). 44 In women, vigorous exercise before pregnancy increases endothelial progenitor cells in umbilical cord blood, which could improve offspring cardiovascular function. 45 Lower toddler weights and weight-for-height z-scores are associated with mothers who engaged in increased leisure-time physical activity during pregnancy.…”
Section: Maternal Exercise and Offspring Metabolic Phenotypesmentioning
confidence: 99%